KONDISI SOSIAL EKONOMI PETANI KELAPA TERHADAP PENDIDIKAN ANAK DI DESA MODAYAMA KECAMATAN KAYOA UTARA KABUPATEN HALMAHERA SELATAN - Alnursa, Darling Surya (Jurnal Pendidikan dan Ekonomi (JUPEK), 2024)
This research aims to determine the socio-economic conditions of coconut farmers regarding children's education in Modayama Village, North Kayoa District, South Halmahera Regency. The type of research used is qualitative with interviews as a data collection technique. The informants in this research were coconut farmers. The stages in data analysis; data collection, data reduction, data display (data presentation), drawing conclusions. At the data validation stage using triangulation techniques. The research results obtained are that the socio-economic conditions of coconut farmers are still below standard or low, this is because the income of coconut farmers, for the majority or around 66.67%, is only IDR. 1,000,000 – Rp.1. 500,000 per harvest. To fulfill their daily needs, around 46.00% of farmers choose side jobs, dominated by fishermen and followed by farmer labor, which reaches 30.00%. Meanwhile, for the highest level of children's education, coconut farmers are able to send their children to high school level, which is around 46.67% and the lowest is at the basic education level with a percentage of 12.33%.